Sarkom hrudní stěny po ozáření pro karcinom prsu kazuistika - Zedníková, I; Safránek, J; Hlaváčková, M; Hes, O; Svoboda, T (Rozhledy v chirurgii, 2014)
INTRODUCTION: Sarcoma occurring in soft tissues after radiotherapy is a rare complication of radiation treatment of tumours. It was most often described after treatment for breast cancer as well as for non-Hodgkin lymphoma and cervical carcinoma. The time interval between the radiation therapy and the development of the sarcoma can be very wide. Treatment demands radical surgical resection of the sarcoma with the edge of the resected tissue without tumour cells. In some cases, this is followed by chemotherapy or radiotherapy. The median survival time is 23 months, the longest survival being associated with sarcomas removed in a radical way. CASE REPORT: We present the case of a female patient with recurring leiomyosarcoma of the chest wall after radiotherapy for cancer of the right breast. In 2006, this 62-year-old patient was operated on to keep her right breast with axilla exenteration. After the surgery, hormonal therapy was followed by adjuvant radiotherapy of the right breast and the adjacent axilla. We used a linear accelerator and the total amount of radiation was 50 Gy (2 Gy fractionally once a day, five days a week). Four years after the operation, leiomyosarcoma was diagnosed in the pectoral muscle at the site where the tumour of the right breast had been excised. Between 2011 and 2013, a total of five operations of re-occurring sarcoma were performed - two excisions of the tumour, a mastectomy, rib resection and, at last, block resection of the chest wall. Adjuvant oncological treatment was not indicated. The patient, now being 69 years old, is still in a good physical and mental condition without any generalization of the disease. CONCLUSION: Sarcoma of the chest wall is a relatively rare consequence of radiotherapy for breast cancer. Sarcoma treatment involves radical surgical resection of the tumour whenever possible. The surgery is mostly followed by radiotherapy which, however, is impossible in a patient after breast-preserving surgery for carcinoma with radiotherapy. Chemotherapy is not very effective in sarcomas. Therefore, the operation needs to be performed by an experienced surgeon in a sufficiently radical way.
Keywords: Breast Neoplasms; Mastectomy; adjuvantní radioterapie; Sarcoma; nádory hrudníku; Middle Aged; Thoracic Wall; ženské pohlaví; Humans; sekundární malignity; sarkom; lidé středního věku; nádory prsu; Thoracic Neoplasms; Female; Radiotherapy, Adjuvant; mastektomie; hrudní stěna; lidé; Neoplasms, Second Primary